(untitled) (Libellarium: journal for research in the field of information and related sciences, 2009)
The aim of this paper is to provide a detailed insight into the issues of preserving rare library materials, and contribute to the possibilities of organizing and managing their continuous preservation, availability and use. The preservation of library materials is a complex issue that can be viewed from different aspects. This paper discusses the basic terminology that is used, with the special focus on rare library materials. The preservation of rare library materials is a seemingly simple and clear term, yet it calls for a more detailed consideration and questioning. The preservation of library materials, in addition to basic issues such as what should it be preserved from, who preserves it, etc., presupposes the establishment of clear links with the mission, functions, framework and the way the institution does its business. The aim of the preservation and all related activities, as well as a full understanding of responsibility, is crucial for the efficient preservation of rare library materials as part of written heritage. The paper presents the concepts and approaches to the protection of library materials in relation to specific methods, techniques and procedures. The preservation of library materials may be viewed at different levels that are intertwined through all concepts and approaches, and this issue is analyzed thoroughly. There is wide range of library materials that are considered as rare. These materials consist of numerous and varied matters that have different durability and characteristics. The criteria of age, value and rarity are also subject to terminological re-examination and should be defined as clearly as possible. Among the important elements in the entire process of preserving rare library materials are management and organization mechanisms. The measures that are undertaken in order to achieve the quality and efficient preservation of rare library materials must be managed purposefully and organized in detail. The efficient management and good organization of preservation presupposes a systematic and comprehensive approach applicable independent of the type of institution or type of material. The management and organization issues concerning the preservation of rare library materials is shown as an overview of their most important elements, with a critical evaluation of the most important achievements in theory in practice. The methodological aspect is also very important in investigating the preservation of rare library materials. The special emphasis is placed on the systematic investigation of the status of library holdings and the possibilities offered by the qualitative and quantitative description of holdings on the one hand, and the possibilities offered by the methods of interview and/or questionnaire on the other. Several practical examples that may serve as test models in the approach to this issue have been analyzed. The existing organization of the collection of historical newspapers from the city of Osijek area, and the organization of the collection of old books in the library of the Franciscan monastery in Mostar in relation to their status and protection activities have also been discussed. By comparing these models a significant difference in the material and content characteristics of the analyzed rare library holdings have been identified. This difference calls for the use of different methodologies for investigating the condition of the holdings. The information on the condition of the library holdings and approaches to their preservation serve as a starting point for planning further steps for the efficient preservation of rare library materials. The insights into the problem of preservation presented in this paper should be understood as a foundation for further implementation on similar examples.